1992
DOI: 10.1002/bdd.2510130607
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of codeine in humans

Abstract: Codeine (30 mg phosphate) was metabolized by eight human volunteers to the following six metabolites: codeine-6-glucuronide 81.0 +/- 9.3 per cent, norcodeine 2.16 +/- 1.44 per cent, morphine 0.56 +/- 0.39 per cent, morphine-3-glucuronide 2.10 +/- 1.24 per cent, morphine-6-glucuronide 0.80 +/- 0.63 per cent, and normorphine 2.44 +/- 2.42 per cent. Two out of eight volunteers were unable to O-dealkylate codeine into morphine and lack therefore the cytochrome P450 IID6 isoenzyme. The half-life of codeine was 1.47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 32 publications
4
52
0
1
Order By: Relevance
“…Both drugs are substrates of cytochrome CYP2D6 and compete with fluoxetine and norfluoxetine as substrates for CYP2D6. 17,18 On discontinuation of fluoxetine, codeine, and tramadol, QTc duration normalized to 434 ms, and TdP did not recur. Genetic screening for CYP2D6 revealed that she was an extensive metabolizer of CYP2D6 with genotype CYP2D6*1/*1.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…Both drugs are substrates of cytochrome CYP2D6 and compete with fluoxetine and norfluoxetine as substrates for CYP2D6. 17,18 On discontinuation of fluoxetine, codeine, and tramadol, QTc duration normalized to 434 ms, and TdP did not recur. Genetic screening for CYP2D6 revealed that she was an extensive metabolizer of CYP2D6 with genotype CYP2D6*1/*1.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…The half-life of codeine is 1.47 8 0.32 h, that of C-6-G 2.75 8 0.79 h. The plasma AUC of C-6-G is approximately 10-fold higher than that of codeine. Protein binding of codeine and C-6-G in vivo was 56.1 8 2.5 and 34.0 8 3.6%, respectively [68] . Codeine metabolic pathways are shown in figure 3 .…”
Section: Codeinementioning
confidence: 99%
“…Quinidine-induced inhibition of codeine O-demethylation is ethnically dependent with the reduction being greater in the Caucasians. Studies performed to date [69][70][71][72][73][74][75][76][77] indicate that codeine analgesia depends on CYP2D6 polymorphism and morphine and the formation of its glucuronides, but codeine and its metabolites (C-6-G and NORC) also contribute to the analgesic effects [66][67][68] .…”
Section: Codeinementioning
confidence: 99%
“…It is metabolized by conjugation to codeine-6-glucuronide and to a minor extent is biotransformed via O-demethylation to morphine and via N-demethylation to norcodeine. 5 Codeine-6-glucuronide is the major metabolite found in urine, whereas codeine is excreted only as a small proportion of the original dose.…”
Section: Discussionmentioning
confidence: 99%